Enhanced Contribution of HLA in Pediatric Onset Ulcerative Colitis. Issue 4 (19th March 2018) - Venkateswaran, Suresh; Prince, Jarod; Cutler, David J; Marigorta, Urko M; Okou, David T; Prahalad, Sampath; Mack, David; Boyle, Brendan; Walters, Thomas; Griffiths, Anne; Sauer, Cary G; LeLeiko, Neal; et al.
Abstract: Background: The genetic contributions to pediatric onset ulcerative colitis (UC), characterized by severe disease and extensive colonic involvement, are largely unknown. In adult onset UC, Genome Wide Association Study (GWAS) has identified numerous loci, most of which have a modest susceptibility risk (OR 0.84–1.14), with the exception of the human leukocyte antigen (HLA) region on Chromosome 6 (OR 3.59). Method: To study the genetic contribution to exclusive pediatric onset UC, a GWAS was performed on 466 cases with 2099 healthy controls using UK Biobank array. SNP2HLA was used to impute classical HLA alleles and their corresponding amino acids, and the results are compared with adult onset UC. Results: HLA explained the almost entire association signal, dominated with 191 single nucleotide polymorphisms (SNPs) (p = 5 x 10 -8 to 5 x 10 -10 ). Although very small effects, established SNPs in adult onset UC loci had similar direction and magnitude in pediatric onset UC. SNP2HLA imputation identified HLA-DRB1*0103 (odds ratio [OR] = 6.941, p = 1.92*10 –13 ) as the most significant association for pediatric UC compared with adult onset UC (OR = 3.59). Further conditioning showed independent effects for HLA-DRB1*1301 (OR = 2.25, p = 7.92*10 –9 ) and another SNP rs17188113 (OR = 0.48, p = 7.56*10 –9 ). Two HLA-DRB1 causal alleles are shared with adult onset UC, while at least 2 signals are unique to pediatric UC. Subsequent stratified analyses indicated that HLA-DRB1*0103 has stronger association for extensive disease (E4: OR = 8.28, p = 4.66x10 -10 ) and female gender (OR = 8.85, p = 4.82x10 -13 ). Conclusion: In pediatric onset UC, the HLA explains almost the entire genetic associations. In addition, the HLA association is approximately twice as strong in pediatric UC compared with adults, due to a combination of novel and shared effects. We speculate the paramount importance of antigenic stimulation either by infectious or noninfectious stimuli as a causal event in pediatric UC onset.